Internal marketing strategies in United Arab Emirates higher education - Muneeb, D.; Tehseen, Shehnaz *; Amin, M.; Kader, F.; Latif, K. L. (Emerald, 2020)
Purpose-This paper seeks to analyze the impact of internal marketing orientations (IMOs) on the competitiveness of higher education institutions (HEIs) in the United Arab Emirates (UAE). Design/methodology/approach-A stratified random sampling was employed to collect data from a pool of 5,968 faculty members in 102 HIEs in the UAE. An online survey questionnaire was placed on Qualtrics online data collection platform and sent to selected participants. Out of a total of 638 surveys send through email, 349 surveys were returned, duly filled. The model was tested using SmartPLS structural equation modeling (PLS-SEM). Findings-IMO dimensions of information generation (IG), information dissemination (ID) and information responsiveness (IR) are inexplicably linked to HEI's competitiveness and faculty performance. IR proved to be a more significant predictor of HEI's competitiveness compared to IG and ID. Practical implications-The study proposes that HEI policymakers encourage the exchange of value among the internal stakeholders and formulate employee-focused policies as part of their corporate objectives. The findings also advocate in improving working conditions and enhancing work–life balance to strengthen the institutions' competitive position within the industry. Originality/value-This study is the first to explore the interrelationship among the IMO dimensions of IG, ID and IR and their impact on HEI competitiveness, particularly in the UAE.